Labour History in the Semi-periphery : Southern Europe, 19th-20th centuries - Andrea, Umberto Gritti; Anna Pina, Paladini; Anna, Pellegrino; Aurora, Iannello; Daniel, Alves; Enric, Garcia-Domingo; Kostas, Paloukis; Leda, Papastefanaki; Maria, Papathanassiou; Milan, Balaban; Nikos, Potamianos; Paolo, Raspadori; et al. (De Gruyter Oldenbourg, 2020)
This collective volume aims at studying a variety of labour history themes in Southern Europe, and investigating the transformations of labour and labour relations that these areas underwent in the 19th and the 20th centuries. The subjects studied include industrial labour relations in Southern Europe; labour on the sea and in the shipyards of the Mediterranean; small enterprises and small land ownership in relation to labour; formal and informal labour; the tendency towards independent work and the role of culture; forms of labour management (from paternalistic policies to the provision of welfare capitalism); the importance of the institutional framework and the wider political context; and women's labour and gender relations.- Resumé vydavatel